Malaria transmission dynamics surrounding the first nationwide long-lasting insecticidal net distribution in Papua New Guinea. (December 2016) - Reimer, Lisa; Thomsen, Edward; Koimbu, Gussy; Keven, John; Mueller, Ivo; Siba, Peter; Kazura, James; Hetzel, Manuel; Zimmerman, Peter
Abstract Background The major malaria vectors of Papua New Guinea exhibit heterogeneities in distribution, biting behaviour and malaria infection levels. Long-lasting, insecticide-treated nets (LLINs), distributed as part of the National Malaria Control Programme, are the primary intervention targeting malaria transmission. This study evaluated the impact of LLINs on anopheline density, species composition, feeding behaviour, and malaria transmission. Methods Mosquitoes were collected by human landing catch in 11 villages from East Sepik Province and Madang Province. Mosquitoes were collected for 3 years (1 year before distribution and 2 years after), and assayed to determine mosquito species andPlasmodium spp. infection prevalence. The influence of weather conditions and the presence of people and animals on biting density was determined. Determinants of biting density and sporozoite prevalence were analysed by generalized estimating equations (GEE). Results Mosquito biting rates and entomological inoculation rates decreased significantly after the distribution.Plasmodium falciparum andP. vivax sporozoite prevalence decreased in year 2, but increased in year 3, suggesting the likelihood of resurgence in transmission if low biting rates are not maintained. An earlier shift in the median biting time ofAnopheles punctulatus andAn. farauti s.s . was observed. However, this was not accompanied by an increase in the proportion of infective bites occurring before 2200 hours. A change in species composition was observed, which resulted in dominance ofAn. punctulatus in Dreikikir region, but a decrease inAn. punctulatus in the Madang region. When controlling for village and study year, An. farauti s.s., An. koliensis andAn. punctulatus were equally likely to carryP. vivax sporozoites. However, An. punctulatus was significantly more likely thanAn. farauti s.s. (OR 0.14; p = 0.007) orAn. koliensis (OR 0.27; p < 0.001) to carryP. falciparum sporozoites. Conclusions LLINs had a significant impact on malaria transmission, despite exophagic and crepuscular feeding behaviours of dominant vectors. Changes in species composition and feeding behaviour were observed, but their epidemiological significance will depend on their durability over time.